Report on the geomorphological, paleomagnetic, geodetic, zoological and botanical field work in the Sør Rondane Mountains, 1988-89 summer season (JARE-30) - Kiichi Moriwaki; Minoru Funaki; Kazuomi Hirakawa; Katsuyasu Tokieda; Hiroshi Abe; Seigo Higashi; Hiromi Miyawaki (National Institute of Polar Research, 1989)
The summer party of the 30th Japanese Antarctic Research Expedition (JARE-30) carried out the geomorphological, paleomagnetic, geodetic, zoological and botanical field work in the western part of the Sør Rondane Mountains for 35 days from December 29,1988 to February 1,1989,and around Asuka Station for 8 days from February 2 to 9,1989. The field work in February was largely hampered by bad weather including blizzard. In addition to earth scientists who have been in charge of the field operation of the Sør Rondane Mountains since JARE-26 (1985), biologists joined the field party for the first time this season under the similar planning and operating scheme formerly adopted. This is the report describing the results of field operations including logistics, a summary of the field work, and some information on weather and surface conditions of snow and ice around the Mountains during this period.